2015
DOI: 10.1080/19420862.2015.1062193
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion interactions with mAbs: Part 1

Abstract: (2015) Metal ion interactions with mAbs: Part 1, mAbs, 7:5, 901-911, DOI: 10.1080DOI: 10. /19420862.2015 To link to this article: https://doi.org/10. 1080/19420862.2015 , can bind to the mAb and undergo hydrolysis or oxidation, which can lead to cleavage of the molecule. To better understand the mechanism of Cu 2C -mediated mAb fragmentation, hinge region cleavage products and their rates of formation were studied as a function of pH with and without Cu 2C . More detailed analysis of the chemical changes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…35,36 In one instance, the mechanism of metal-induced mAb fragmentation was studied where Cu (2C) -mediated fragmentation was determined to occur predominantly through a hydrolytic pathway in solution. 11 In our study, the observed higher tendency of fragmentation may be a result of selection bias during formulation optimization, wherein aggregation is considered as a more significant quality attribute than fragmentation, primarily due to immunogenicity concerns. [37][38][39] While our results suggest that aggregation-driven degradation may be predictive when using conventional biophysical characterization techniques, prediction of fragmentation was not well correlated to stability data.…”
Section: Discussionmentioning
confidence: 94%
“…35,36 In one instance, the mechanism of metal-induced mAb fragmentation was studied where Cu (2C) -mediated fragmentation was determined to occur predominantly through a hydrolytic pathway in solution. 11 In our study, the observed higher tendency of fragmentation may be a result of selection bias during formulation optimization, wherein aggregation is considered as a more significant quality attribute than fragmentation, primarily due to immunogenicity concerns. [37][38][39] While our results suggest that aggregation-driven degradation may be predictive when using conventional biophysical characterization techniques, prediction of fragmentation was not well correlated to stability data.…”
Section: Discussionmentioning
confidence: 94%
“…21 It is possible that inserting the scFv at the IgG1 hinge may increase metal-mediated cleavage at the hinge due to increased flexibility and better solvent accessibility.…”
Section: Molecular Design Of Bs4abmentioning
confidence: 99%
“…However, copper chloride and an immunoglobulin F(ab') 2 showed a robust antagonistic effect. There has been reported in the literature that copper ions could induce IgG cleavage [33,34]. Past research had found that when metal ions were present in a specific stereochemistry in the appropriate conformation, metal ions could increase the rate of peptide cleavage and catalyze the reaction [35,36].…”
Section: Discussionmentioning
confidence: 99%